Study of Ni-dopped MnCo2O4 Yolk-Shell Submicron-spheres with Fast Li+ Intercalation Pseudocapacitance As An Anode for High-Performance Lithium Ion Batteries. (10th June 2016) - Wu, Lijun; Lang, Junwei; Wang, Shuai; Zhang, Peng; Yan, Xingbin
Abstract: Spinel Ni-dopped MnCo2 O4 powder with fast Li + intercalation pseudocapacitance is prepared from transition metal carbonates of Ni, Co and Mn as precursors through a solvothermal synthesis followed by an annealing treatment. As-made products are nanovoids submicron-spheres (the diameter is 500 nm–700 nm) with an obvious yolk-shell structure and uniform elements distribution. As an anode material with fast Li + intercalation pseudocapacitance for lithium-ion battery (LIB), the Ni-dopped MnCo2 O4 submicron-spheres exhibit an impressively first discharge efficiency (70%) and outstanding large-current cycling performance. The excellent electrochemical performance is closely ascribed to Li + intercalation pseudocapacitance and the yolk-shell structure, which can effectively prevent the particles from being pulverized, and alleviate the volume changes of particles during the cycling process. In addition, the doping of Ni metal element to MnCo2 O4 greatly enhances the electrochemical stability of MnCo2 O4, due to the complementarities and synergies between the three metallic elements during the process of Li insertion or extraction reactions.